Pregnancy planning in lupus and APS patients - Haase, Isabell; Fischer-Betz, Rebecca (Frontiers in Lupus, 2024)
Systemic Lupus Erythematosus (SLE) and Antiphospholipid Syndrome (APS) have a substantial impact on pregnancy outcomes and require meticulous planning and management. This article explores the complex interrelationships between SLE, APS, and pregnancy and provides an overview of the associated risks and predictors. The crucial role of pre-conception counselling, risk stratification and tailored treatment plans is highlighted, accompanied by a suggested practical approach. Recent advancements in therapeutic approaches and emerging research on promising targeted interventions indicate the potential for enhanced maternal and fetal outcomes.